Efektivitas Fitoremediasi Limbah Detergen: Kajian Literatur - Tiara Zahira; Nurul Fadillah; Yahya Ayasy Al-Muhandis (Jurnal Biodiversitas dan Bioteknologi, 2025)
The increasing use of detergents increases the risk of environmental pollution. Detergent waste can cause a decrease in water quality so that it is no longer suitable for consumption, use, and disrupts the balance of the aquatic ecosystem which has a negative impact on the lives of aquatic organisms. Therefore, environmentally friendly waste management techniques such as phytoremediation are needed. The purpose of writing this review article is to analyze the potential, mechanisms, determine the factors that influence effectiveness, and examine the advantages and disadvantages of detergent waste phytoremediation. Journal writing is done using the literature review method. From a number of literatures found, literature was selected that contained discussions related to the topic and purpose of writing the journal. From a number of literatures, it is known that plants that have the potential to be agents for phytoremediation of detergent waste are Pistia stratiotes L., Acanthus ilicifolius, Marsilea crenata, Acanthus montanus, Pistia stratiotes, Sagittaria lancifolia, Eichornia crassipes, Actinoscirpus grossus, Thypa Angustifolia L., Echinodorus palaefolius, Monochoria vaginalis, Lemna minor, Azolla microphylla, and Ludwigia adscendens. Phytoremediation mechanisms include phytostabilization, rhizofiltration, phytodegradation, phytoextraction, and phytovolatilization. The effectiveness of phytoremediation is influenced by detergent concentration, number of plants, temperature, pH, and duration of treatment. Phytoremediation methods are environmentally friendly because they do not involve chemicals or processes that can damage the environment, but they require optimization because the capacity of each plant to process waste varies. Large-scale phytoremediation applications require consideration of factors that affect the effectiveness of each plant.